Endoscopic Transsphenoidal Surgery of Pituitary Adenomas: Preliminary Results of the Neurosurgery Service of Hospital Cristo Redentor - Perondi, Gerson; Mariante, Afonso; Azambuja, Fernando; Greggianin, Gabriel Frizon; Dias, Wanderson William dos Santos; Pinzetta, Giulia (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Objective The transsphenoidal surgery is a safe and effective technique to manage different skull base pathologies, such as pituitary adenomas. The purpose of the present study is to describe the initial experience with endoscopic transsphenoidal surgery in the treatment of pituitary adenoma patients at a tertiary hospital that is a reference in neurosurgery in Southern Brazil.Materials and Methods We retrospectively analyzed data from 60 patients with pituitary adenoma who underwent endoscopic transsphenoidal surgery between 2012 and 2019. Demographic characteristics, type of tumor, baseline hormonal changes, and clinical presentation were reported, as well as postoperative outcomes, tumor resection rate, and complications.Results The male/female ratio was of 0.53:1, and the mean age of the sample was of 54 (range: 26 to 79) years. In total, 34 patients (57%) presented the non-functioning adenoma subtype, and 26 (43%), the functioning adenoma subtype. In the non-functioning and functioning subtype groups, the average tumor diameter was of 32 mm and 18 mm, and the mean follow-up was of 27 months and 32 months respectively. Regarding visual symptoms, 79% of the patients showed improvement after surgery. Hormonal remission was achieved in 71% of the patients with prolactinoma, 85% of those with cushing, and 57% of patients with acromegaly. Overall, gross total resection (GTR) was achieved in 50% of patients but with a significantly lower rate among patients with tumors with parasellar growth (high grade on the Knosp classification). The most prevalent surgical complications observed were postoperative cerebrospinal fluid (CSF) leak and meningitis in 11% and 6% of the cases respectively.Conclusion We have shown that transsphenoidal endoscopic surgery can produce good results in the management of pituitary adenomas, with acceptable peri- and postoperative morbidity and mortality. Regardless of the technique used, the presence of large and giant pituitary adenomas with a high Knosp grade represents an enormous challenge for contemporary neurosurgery.
Keywords: endoscopic surgery; pituitary gland; epidemiology; adenoma